Edukasi dan Pendampingan Pemilahan Timbulan Sampah Peserta Bumi Perkemahan Desa Wisata Tinalah - Sipayung, Renan J. Indra; Morib, Margeritha Agustina; Widiastuti, Widiastuti; Ariyani, Ninik; Wikana, Iwan; Heriadi, Heriadi; Harianja, Jhonson Andar; Bangguna, David S. V. L.; Sanam, Melvi; Sanam, Adel Faniati; Mahardika, Daniswara Indra; Putra, Only Jeje A. (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Tinalah Tourism Village is a natural tourism destination located in Purwoharjo Village, Samigaluh District, Kulon Progo Regency, Yogyakarta. Tinalah Tourism Village is growing with increasing tourist visits, camping activities. The increase in tourists has caused an increase in waste generation. Based on observations that waste in the Camping Ground environment has so far been carried out by piling up and burning, not implementing a recycling and reuse system. This Community Service Activity aims to raise awareness among camp participants in the importance of waste management by implementing the principle of a circular economy. The Community Service Activity for waste measurement education was enthusiastically welcomed by the managers of the Tinalah Tourism Village Camping Ground, scout leaders and camp participants. The waste produced is inorganic waste (paper, plastic), and organic waste (food scraps).